Strategi Implementasi Pembelajaran Berdiferensiasi Diera Kurikulum Merdeka - Daniar Rahmah Dinita; Laelia Nurpratiwiningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The research focuses on contributing to the challenges of implementing differential learning by presenting strategies for its effective application. Utilizing qualitative research designs, the study aims to understand how to implement differential learning strategies in the context of independent curricula. The exploration of literature allows researchers to investigate differential learning phenomena in real-life and complex situations. Essentially, differential learning is adaptable and modifiable for various subjects and materials (Pramudianti et al., 2023). Achieving optimal implementation requires attention to learning syntax, encompassing planning, implementation, monitoring, and evaluation) (Hasanah et al., 2023). Integration of these processes is vital for success, with teachers engaging in reflective practices during evaluations. The results indicate that differential learning implementation, tailored to individual readiness, styles, and interests, enhances student talent and interest for more effective learning outcomes (Lukitoaji & Komalasari, 2023). Three key strategies within differential learning – content differentiation, process differentiation, and product differentiation – contribute to achieving optimum learning (Sarie, 2022). The research underscores the importance of meticulous planning and integration in the differential learning process, fostering a tailored and effective educational experience.